About the possibility of the estimation of superficial potential of semiconductor films from thickness dependence of kinetic factors - Ermaganbetov, K.T.; Chirkova, L.V. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
In work the expressions describing dependences of kinetic factors of carriers of a charge from a thickness of semiconductor films at certain values of superficial potential are received. The estimation of a value of superficial electrostatic potential in films p-Ge on the basis of experimental data on research of thick dependences of kinetic factors is resulted. Satisfactory conformity of values of the superficial potential received by a calculating way and from experimental data is established.
Keywords: semiconductor films; superficial potential; kinetic factors; films p-Ge